Tradisi Nurunkan Kupek dan Relevansinya Dengan Nilai-Nilai Pendidikan Agama Islam Di Desa Bangun Jaya Kecamatan Tanjung Batu Kabupaten Ogan Ilir - Gia Rosdiana Tirta; Dwi Noviani (STIKes Ibnu Sina Ajibarang, 2023)
Tradition is a habit that is based on a belief or belief in something done by a person or community whose existence has been introduced from the past until now by ancestors from generation to generation and cannot be eliminated. The aim of this research is to find out and develop the process of a tradition carried out in Bangun Jaya Village in everyday life. The research method used in this research is qualitative descriptive research using documents and books as data sources. In addition, researchers also conducted interviews as supporting data in this research. The results of this research regarding the traditions carried out by the Bangun Jaya community in their daily lives have a positive impact, traditions like this can be a link between kinship and the introduction of new members.